Detection of Spread-out Position for Pulse Changing-state of Porous Material-object in Dermis Layer - Kim, Jeong L.; Im, Yong S.; Park, Jong Y.; Jang, Kyeong S.; Choi, Gyoo S.; Kang, Jeong J. (International Journal of Membrane Science and Technology, 2023)
Grainy surface of moist skin is a stalk transition by grain transport containing monolayer or multilayer multiblock modules as superconductors. Brilliant-differentiation cognition level (BIAL) is conveyed the stiff spread-out-sonance status within the skin to the stalk cognition level function and used a technique of mixing by pulse change. In order to observe the spread-out-sonance status within the skin with the stalk conveyance function, the stalk value with ductile-dot was found and calculated by the superstructure. In the dermis layer, the criterion of brilliant-differentiation level is transition signal by stalk sonance function. Configured as the cognition level and the technical concept of pulse change was measured by the diffusion sonance function that converted into BIAL value by the maximum average. According to the degree of water distribution in the skin, the degree of pulse change was configured as the cognition level of the sonance function, and the value was formed. Stalk ductile-dot sonance presented stalk far transition value of St-CF-FA-?MAX-MED with 11.34±5.57 units. Stalk convenient transition value presented St-CF-CO-?MAX-MED with 2.04±0.51 units. Stalk flank transition value presented St-CF-ST-?MAX-MED with 1.21±0.18 units. Stalk vicinage transition value presented St-CF-VI-?MAX-MED with 0.19±0.11 units. As the degree of ability of the ductile-dot is evaluated spread-out sonance by diffusion function that appeared at the stalk cognition level of the porous material-object by BIAL in the dermis layer. As a differentiation function can be used by the conveyance level system of the dermis layer. Diffusion cognition systems are suppressed by differential signals. Cognition systems is able to exploit the data as promising primary tools for analyzing surfaces from fundamental applications and nanotechnology perspectives.